2020
DOI: 10.1134/s2517751620050030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crosslinking Agent Length on the Transport Properties of Polydecylmethylsiloxane-Based Membranes

Abstract: The effect of crosslinking agent length on transport properties of membranes based on polydecylmethylsiloxane (PDecMS) has been studied. Dense PDecMS membranes reinforced with a stainless-steel grid and crosslinked with either 1,7-octadiene or vinyl-terminated polydimethylsiloxane (M n = 500 g/mol) have been synthesized. The permeability of light hydrocarbons (methane, propane, n-butane) and separation characteristics of the membranes have been studied using an eight-component model mixture simulating the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The general trend is a decrease in mass transfer and selectivity, with a decrease in the concentration of ethylene in the initial mixture. This is not surprising, since the mass transfer coefficient depends on the concentration [49].…”
Section: Ethylene/ethane Separation In Membrane Contactor Gas-liquidmentioning
confidence: 88%
See 2 more Smart Citations
“…The general trend is a decrease in mass transfer and selectivity, with a decrease in the concentration of ethylene in the initial mixture. This is not surprising, since the mass transfer coefficient depends on the concentration [49].…”
Section: Ethylene/ethane Separation In Membrane Contactor Gas-liquidmentioning
confidence: 88%
“…The general trend is a decrease in mass transfer and selectivity, with a decrease in the concentration of ethylene in the initial mixture. This is not surprising, since the mass transfer coefficient depends on the concentration [49]. In this case, the qualitative difference in the separating ability of Ag9/MFFK and POMS/MFFK membranes seems to be of interest.…”
Section: Ethylene/ethane Separation In Membrane Contactor Gas-liquidmentioning
confidence: 90%
See 1 more Smart Citation
“…Performing the modification and cross-linking by hydrosilylation allows also using a single catalyst, which improves the economic efficiency of this approach. The simplicity of the suggested procedure allowed us to study in our subsequent works how various crosslinking agents influence the gas-transport properties of membranes based on polyoctylmethylsiloxane (POMS) [72] and polydecylmethylsiloxane [73]. As we showed, an increase in the length of the cross-linking agent, divinyltetramethyldisiloxane-PDMS (M n = 25000 g mol -1 ), leads to a decrease in the ideal n-butane/ methane selectivity from 26 to 22 and to an increase in the permeability coefficient (from 9600 to 9800 Barrer at the pressure over the membrane of 0.8 bar) [72].…”
Section: Pendant Chain Modificationmentioning
confidence: 99%
“…We also noted that the introduction of a larger amount of poly(octylmethylsiloxane) leads to a decrease in the cross-link density and an increase in the permeability and selectivity of the material for VOC vapors. It was demonstrated that the use of a shorter cross-link made it possible to increase the selectivity of n-butane with respect to methane while maintaining the permeability of n-butane at a comparable level [26].…”
Section: Introductionmentioning
confidence: 99%